In Vivo Sensitivity of Blue-Light-Dependent Signaling Mediated by AppA/PpsR or PrrB/PrrA in Rhodobacter sphaeroides - Metz, Sebastian (American Society for Microbiology (ASM), 2009)
Formation of photosynthesis complexes in Rhodobacter sphaeroides is regulated in a redox- and light-dependent manner by the AppA/PpsR and PrrB/PrrA systems. While on the one hand, blue light is sensed by the flavin adenine dinucleotide-binding BLUF domain of AppA, on the other, light is absorbed by bacteriochlorophyll signals through PrrB/PrrA. We show that much smaller quantities initiate the AppA-mediated response to blue light than the bacteriochlorophyll-mediated response.